The Cold Hand Sign in Multiple System Atrophy: Frequency-Associated Factors and Its Impact on Survival - Cao, Bei; Liang, Yan; Zhang, Ling-Yu; Hou, Yan-Bing; Ou, Ru-Wei; Wei, Qian-qian; Shang, Huifang (Frontiers in Aging Neuroscience, 2021)
Background: Few studies have focused on the cold hand sign (CHS), a red flag symptom, in multiple system atrophy (MSA). Objective: This study aimed to investigate the frequency and correlative factors of CHS in patients with MSA and the impact of its early occurrence on the survival of these patients. Methods: A total of 483 patients with MSA were enrolled in this study, and the motor and non-motor symptoms between patients with MSA with and without CHS were compared. Moreover, patients with disease duration ≤ 3 years at baseline were followed, and the association between CHS and survival of patients with MSA was examined. Results: The frequencies of CHS in patients with MSA were 20, 15.4, and 25.3% in MSA, MSA-parkinsonian subtype (MSA-P), and MSA-cerebellar subtype (MSA-C), respectively. Higher Unified Multiple System Atrophy Rating Scale (UMSARS) scores and higher Non-Motor Symptom Scale (NMSS) scores at baseline were associated with CHS in MSA. CHS was associated with shorter survival after adjusting for baseline diagnosis subtype, age at onset, sex, orthostatic hypotension, disease duration, autonomic onset, UMSARS total score, and NMSS score (p = 0.001; HR = 3.701; 95% CI = 1.765–7.760). Conclusion: CHS is not rare in patients with MSA. Greater disease severity and more severe non-motor symptoms were associated with CHS in patients with MSA. Patients with early occurrence of CHS had a poor prognosis.